PMCA2 regulates HER2 protein kinase localization and signaling and promotes HER2-mediated breast cancer - Jeong, Jaekwang (Proc Natl Acad Sci U S A, 2016)
In the lactating mammary gland, the plasma membrane calcium ATPase2 (PMCA2) transports milk calcium. Its expression is activated in breast cancers, where high tumor levels predict increased mortality. We find that PMCA2 expression correlates with HER2 levels in breast cancers and that PMCA2 interacts with HER2 in specific actin-rich membrane domains. Knocking down PMCA2 increases intracellular calcium, disrupts interactions between HER2 and HSP-90, inhibits HER2 signaling, and results in internalization and degradation of HER2. Manipulating PMCA2 levels regulates the growth of breast cancer cells, and knocking out PMCA2 inhibits the formation of tumors in mouse mammary tumor virus (MMTV)-Neu mice. These data reveal previously unappreciated molecular interactions regulating HER2 localization, membrane retention, and signaling, as well as the ability of HER2 to generate breast tumors, suggesting that interactions between PMCA2 and HER2 may represent therapeutic targets for breast cancer.